PARAMETERS OF BLINK REFLEX AND EVOKED BRAIN POTENTIALS ON ESTIMATION OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION EFFECTIVITY AT EPILEPSY - O. V. Kistsen (Эпилепсия и пароксизмальные состояния)
Abstract: The article content results of estimation of Blink Reflex and evoked brain potentials (cognitive and visual) parameters changes on epilepsy patients, which treated by anticonvulsants and repetitive transcranial magnetic stimulation course (rTMS). Data of Blink Reflex parameters on dependence from epileptic process activity were given. Received data define some aspects of epilepsy pathogenesis and widen conception about long-lasting processes of brain reaction after short rTMS course.